Pengaruh Modifikasi Latihan Model Superman Terhadap Peningkatan Daya Tahan Otot Punggung - Ramdani, Handi; Sutisna, Nana; Hartono, Tony (Jurnal Keolahragaan, 2023)
This research aims to determine the increase in back muscle endurance. The research method used is pre-experimental design. The test instrument used is the back lift test. The research location was held at SSB Bhineka Futsal, Majenang District, Cilacap Regency with a total of 40 students for two research groups. This research shows the following results: 1. Superman training has a significant impact on increasing back muscle endurance in SSB Bhineka Futsal students, Majenang District, Cilacap Regency. 2. The alternating superman exercise affects increasing the back muscle endurance of SSB Bhineka Futsal students, Majenang District, Regency. 3. SSB Bhineka Futsal students from Majenang District, Cilacap Regency showed a significant increase in back muscle endurance which is different from alternating superman training compared to superman training. Conclusion: SSB Bhineka Futsal students from Majenang District, Cilacap Regency showed an increase in back muscle endurance after doing superman training and superman alternation.